Cardiomyocyte Regulation of Systemic Lipid Metabolism by the Apolipoprotein B-Containing Lipoproteins in Drosophila. - Sunji Lee; Hong Bao; Zachary Ishikawa; Weidong Wang; Hui-Ying Lim (PLoS Genetics, 2017)
The heart has emerged as an important organ in the regulation of systemic lipid homeostasis; however, the underlying mechanism remains poorly understood. Here, we show that Drosophila cardiomyocytes regulate systemic lipid metabolism by producing apolipoprotein B-containing lipoproteins (apoB-lipoproteins), essential lipid carriers that are so far known to be generated only in the fat body. In a Drosophila genetic screen, we discovered that when haplo-insufficient, microsomal triglyceride transfer protein (mtp), required for the biosynthesis of apoB-lipoproteins, suppressed the development of diet-induced obesity. Tissue-specific inhibition of Mtp revealed that whereas knockdown of mtp only in the fat body decreases systemic triglyceride (TG) content on normal food diet (NFD) as expected, knockdown of mtp only in the cardiomyocytes also equally decreases systemic TG content on NFD, suggesting that the cardiomyocyte- and fat body-derived apoB-lipoproteins serve similarly important roles in regulating whole-body lipid metabolism. Unexpectedly, on high fat diet (HFD), knockdown of mtp in the cardiomyocytes, but not in fat body, protects against the gain in systemic TG levels. We further showed that inhibition of the Drosophila apoB homologue, apolipophorin or apoLpp, another gene essential for apoB-lipoprotein biosynthesis, affects systemic TG levels similarly to that of Mtp inhibition in the cardiomyocytes on NFD or HFD. Finally, we determined that HFD differentially alters Mtp and apoLpp expression in the cardiomyocytes versus the fat body, culminating in higher Mtp and apoLpp levels in the cardiomyocytes than in fat body and possibly underlying the predominant role of cardiomyocyte-derived apoB-lipoproteins in lipid metabolic regulation. Our findings reveal a novel and significant function of heart-mediated apoB-lipoproteins in controlling lipid homeostasis.